Highlights in gravitational lensing - Bartelmann, Matthias (Classical and quantum gravity, 1993)
Gravitational lensing is reviewed emphasising its importance as an astrophysical tool. The theoretical concepts are briefly introduced and applications of the theory to astrophysical observations are discussed. From individual gravitational lens systems one can determine lens masses, estimate the sizes, the geometry, and the nature of emitting regions, and measure length scales, of which the Hubble constant is the most important. Statistical gravitational lensing is not considered.